Impact of Color on the Psychological Dimension of the Users of Interior spaces in Hospitals - General Hospital in Sulaimani city as a case study - Ali, Alan Fraidoon; Mahmood, Fouad Jalal (Sulaimani Journal for Engineering Sciences, 2017)
The research aims to identify the effect of color on human health in general and psychological dimension, in particular, to enhance the performance of the interior spaces of hospitals by studying the used colors with the possibility of proper utilizing of it with user psychology and health in hospitals spaces. The study also aims to identify the implications of color expression and its impact on the interior design of hospitals and reaching solutions and suggestions achieving greater understanding of color and its utilizing to enhance the efficiency of the hospital spaces . The research follows descriptive and analytical methods which have been utilized through the description and analysis of the colors of some of the internal spaces of the selected public hospitals building in the city of Sulaimani, as Case Study. Furthermore, the search adopted field interviews of a group of specialists and users of those architectural spaces with different functions to find out the role of psychological effects of colors on it, and then determine the final conclusions and that is the existence of the possibility of the use of color to improve the psychological state of the patients, users of the internal spaces of hospitals and to help accelerating the healing process.
Keywords: Colors; Psychological dimension; Hospitals; Interior Spaces